Методологічні аспекти управління кредитоспроможністю підприємств - Бровко, Лариса Іванівна; Brovko, Larysa; Карпова, Д. Д.; Karpova, D. (Дніпровський державний аграрно-економічний університет, 2021)
Стаття присвячена вивченню методологічних аспектів кредитоспроможності аграрних підприємств України. Розкрито таке поняття, як «фінансові ресурси» та їх вплив на діяльність підприємства. Механізм утворення фінансових ресурсів за рахунок позикових коштів. Наведено основні проблеми, що впливають на формування фінансових ресурсів організації. Також в статті розглянуто різні погляди вчених на визначення поняття «кредитоспроможність». Визначено основні етапи управління конкурентоспроможністю в системі фінансово-економічної безпеки підприємства. Автором досліджено джерела формування фінансових ресурсів товаровиробників, роль кредитоспроможності при використанні зовнішніх джерел фінансування та методи її оцінки. Охарактеризовано фінансові показники, які використовуються для оцінки кредитоспроможності підприємств. Проведено аналіз основних показників кредитоспроможності українських підприємств. Наведено головні критерії та фактори які впливають на кредитоспроможність та способи, які допоможуть підвищити рівень кредитоспроможності підприємств. Доведено, що для покращення управління кредитоспроможністю підприємств необхідно насамперед оптимізувати структуру його капіталу. The article is devoted to determining the methodological aspects of the creditworthiness of enterprises of Ukraine. The concept of "financial resources" and their impact on the enterprises and the mechanism of formation of financial resources at the expense of borrowed funds were disclosed. Assessing the level of financial resources of the enterprise, finding sources of their formation, planning and determining the effectiveness of their use helps the company making its strategic management decisions. The author investigates the sources of formation of financial resources of producers, the role of creditworthiness in the use of external sources of financing and methods of its evaluation. The main problems influencing the formation of financial resources of the organization are given. The article also considers different views of scientists on the definition of "creditworthiness". The need for creditworthiness assessment is substantiated. He article also of competitiveness management in the system of financial and economic security of the enterprise are determined. Assessing the level of financial resources of the enterprise, finding sources of their formation, planning and determining the effectiveness of their use helps the company making its strategic management decisions. The financial indicators used to assess the creditworthiness of enterprises are described. The analysis of the main indicators of creditworthiness of Ukrainian enterprises is carried out. It is concluded that for proper and rational management of creditworthiness in the enterprise it is necessary to conduct a systematic analysis of both internal and external environment using modern scientific approaches to the choice of assessment methods and management mechanisms. The process of managing the creditworthiness of the enterprise itself depends not only on what activities the company conducts, but also on the state of the banking sector of the state. The main criteria and factors that affect the creditworthiness and ways to help increase the level of creditworthiness of enterprises are presented. It is proved that in order to improve the creditworthiness management of enterprises, it is first necessary to optimize the structure of its capital.
Methodological aspects of credit capacity management of enterprises
Keywords: виробництво; production; управління; management; підприємство; enterprise; фінансові ресурси; financial resources; кредитоспроможність; creditworthiness; капітал; capital